BEBERAPA SIFAT HIMPUNAN KRITIS PADA PELABELAN AJAIB GRAF BANANA TREE - Triyani Triyani; Irham Taufiq (Universitas Jenderal Soedirman, 2012)
A critical set in edge magic total labeling on graph G is a subset label such that it can forms the edge magic total labeling uniquely. This paper investigate critical set on Banana Tree graph. The result shows some properties of critical set on Banana Tree graph, such as the size of it at least , where n is number of leaf and k is number of star, except the size of critical set on graph BT(1,1) is 2. Beside it, if x is the label of any leaf and y is the label of the edge adjacent to it then each critical set in λ must contain either x or y, not both.